Optimization of Built Environment and Structural Configuration for Rail-Airport Intermodal Transfer Systems: Evidence from Adi Soemarmo Airport, Surakarta - hana wp; Efendhi Prih Raharjo; Anisa Mahadita Candrarahayu (Indonesia Civil Pilot Academy Banyuwagi, 2026)
This study aims to evaluate the level of multimodal transport integration between rail services and airport facilities using the Intermodal Seamless Mobility (ISM) approach at Bandar Udara Adi Soemarmo, Indonesia. A quantitative descriptive case study method was employed through field observations and direct measurement of three key indicators: Walking Distance (WD), Transfer Time (TT), and Baggage Friction Index (BFI). These indicators were normalized and synthesized into the Intermodal Seamless Mobility Index (ISMI) to assess the quality of passenger transfer connectivity. The results indicate a Walking Distance of 146 m, Transfer Time of 4 min, and BFI of 0.547. Based on the weighted indicator model, the calculated ISMI value was 0.6697, which falls within the Good Seamless category. This finding suggests that passenger transfer from the railway station to the airport terminal is relatively efficient, convenient, and functionally integrated. However, further improvements are required to achieve the Highly Seamless category, particularly through baggage-handling facilities enhancement, additional travelators, improved wayfinding systems, and stronger intermodal information integration.